International Trade, Distortions and Long-Run Economic Growth - Lee, Jong-Wha (International Monetary Fund, 1992)
The links between trade and growth are examined in a neoclassical model of an open economy in which domestic production requires both domestic and imported inputs. The model shows that trade distortions induced by such government policies as tariffs and exchange controls generate cross-country divergences in growth rates and in per capita income over a long transitional period. The empirical results confirm that tariff rates and black market premia, interacting with an estimate of the share of free trade imports, have significant negative effects on the growth rate of per capita income across countries in the orders of magnitude predicted by the model